A Call for Examining Replication and Bias in Special Education Research. (July 2014) - Cook, Bryan G.
Valid, scientific research is critical for ascertaining the effects of instructional techniques on learners with disabilities and for guiding effective special education practice and policy. Researchers in fields such as psychology and medicine have identified serious and widespread shortcomings in their research literatures related to replication and bias, leading many to question the validity of research findings in these fields. Replication and bias have not been systematically examined in special education research. In this article, I explore research on replication and bias conducted in other fields, discuss the likelihood that problems in replication and bias may exist in the special education research base, propose a research agenda for investigating replication and bias in special education research, and make initial recommendations for increasing replication and reducing bias in intervention studies in special education.